Differing effects of oral conjugated equine estrogen and transdermal estradiol on vitamin D metabolism in postmenopausal women: a 4-year longitudinal study. Issue 10 (20th August 2022) - Santoro, Anna Maria; Simpson, Christine A.; Cong, Elaine; Haas, Andrea; Sullivan, Rebecca R.; Parziale, Stephen; Deng, Yanhong; Insogna, Karl L.
Abstract : The findings of this study imply that there may be a short-term benefit to prescribing transdermal estradiol for women who are either vitamin D deficient or vitamin D insufficient. Abstract: Objective: The aim of this study was to examine the effect of either conjugated equine estrogen or transdermal estradiol on vitamin D metabolism in postmenopausal women. Methods: Twenty-five women from the Kronos Early Estrogen Prevention Study who were randomized to conjugated equine estrogen 0.45 mg/d and 20 women who were treated with transdermal estradiol 50 mg/d (patch replaced weekly) were analyzed in the present study. All participants received micronized progesterone for 12 days per month. Results: There was no significant treatment effect on serum total 25-hydroxyvitamin D over 48 months in either study group, and there were no significant differences between treatment arms. In contrast, at 12 months, directly measured free 25-hydroxyvitamin D was significantly higher in the transdermal estradiol group than in the conjugated equine estrogen group. Directly measured free 25-hydroxyvitamin D subsequently increased significantly from 12 to 48 months in both treatment arms. Calculated free 25-hydroxyvitamin D was also significantly higher in the transdermal estradiol group at 36 months. Vitamin D–binding protein decreased significantly in both treatment groups from 12 to 48 months, but at 48 months, least square mean values were no different based on treatment assignment. Conclusions: Directly measured free 25-hydroxyvitamin D levels, but not serum total 25-hydroxyvitamin D levels, are different within the first 12 months of estrogen replacement depending on the preparation. However, this difference is transient, in that there were no differences at 36 or 48 months. These findings suggest that there may be a short-term benefit to prescribing transdermal estradiol for women who are either vitamin D deficient or vitamin D insufficient.